CONTROL AND SENSING SYSTEM FOR DIFFUSION OPTICAL TOMOGRAPHY AND METHOD FOR OPERATING THE SAME - Fang Wai-Chi; Chen Tien-Ho; Kang Shih; Wu Shih-Yang; Cheng Ching-Ju (My University, 2013)
A control and sensing system for diffusion optical tomography and a method for operating the same are disclosed. The control and sensing system includes a control unit and a sensing circuit with a plurality of light sources and sensors, each light source being surrounded by a corresponding predetermined number of the sensors. The control unit instructs the light sources to individually emit light to an object, so the object generates a plurality of optical signals, and instructs the predetermined number of the sensors corresponding to each light source to receive the optical signals and transmit them to the control unit, thereby reducing the complexity of the control and sensing system.